Good-for-Nothing Entrepreneurs: Capitalism and Democratic Decline in the West - Wim Naudé (Institute of Labor Economics (IZA), 2025)
This paper focuses on the relationship between capitalism and the decline in democracy in the West over the past quarter-century. Using data from the V-Dem Institute, Freedom House, and the World Inequality Database, a strong correlation is found between inequality, the rise of tech billionaires, and democratic erosion. This correlation is explained by describing how tech oligarchs grow their political influence through their digital platforms, and their societal control via surveillance and influence of sense-making. The pivot of tech oligarchs toward the Military Industrial Complex (MIC) will accelerate the erosion of democracy. The implication is that efforts to regulate the digital economy to protect democracy will not be effective unless accompanied by decisive measures to break up the oligarchy and dismantle the Permanent War Economy.
Keywords: P16; D31; O33; O40; 330; democracy; oligarchy; inequality; capitalism